Application of the Discovery Learning Model to Improve Student Learning - Indayana Febriani Tanjung; Anisya Agustina; Sarah Yulinda; Octavia Chotimah; Hanifah Dinda Difanie (Edumaspul: Jurnal Pendidikan, 2022)
An effort to improve the learning process through the application of the Discovery Learning method. The formulation of the problem in this study is whether the use of the Discovery Learning method can improve learning outcomes for Biology subjects for class X MAS Al Wasliyah students in the 2022/2023 academic year range? learning by using the Discovery Learning method. The purpose of this research is to improve the Biology learning process for the tenth grade students of Mas Alwasliyah Range in the 2022/2023 academic year. This research uses the CAR model with the application of the Discovery Learning method in improving the learning outcomes of Biology subjects for class X Mas Alwasliyah students in the 2022/2023 academic year range. The data was collected by observing student activities and worksheets to find out the improvement in student learning outcomes. From the results of the analysis that has been carried out, it is known that the Discovery Learning learning method can improve student learning outcomes for Biology subjects at MAS Al Wasliyah. 95%. So it can be concluded that using Discovery Learning can improve learning outcomes in the Biology learning process for class X MAS Alwasliyah students in the 2022/2023 academic year range.